2005
DOI: 10.1016/j.cub.2005.01.050
|View full text |Cite
|
Sign up to set email alerts
|

A Steric-Inhibition Model for Regulation of Nucleotide Exchange via the Dock180 Family of GEFs

Abstract: CDM (CED-5, Dock180, Myoblast city) family members have been recently identified as novel, evolutionarily conserved guanine nucleotide exchange factors (GEFs) for Rho-family GTPases . They regulate multiple processes, including embryonic development, cell migration, apoptotic-cell engulfment, tumor invasion, and HIV-1 infection, in diverse model systems . However, the mechanism(s) of regulation of CDM proteins has not been well understood. Here, our studies on the prototype member Dock180 reveal a steric-inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
117
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(125 citation statements)
references
References 22 publications
7
117
1
Order By: Relevance
“…Similar to Dock180, Dock4 interacts with ELMO2 through its SH3 domain (Fig. 6C) (31). Dock4-SH3 and SH3-L showed a similar binding ability to ELMO2 as Dock4-FL, suggesting that these fragments act as competitive binding partners of Dock4 (Fig.…”
Section: Expression Pattern Of Dock4 In the Brain-to Gain Insightsmentioning
confidence: 77%
“…Similar to Dock180, Dock4 interacts with ELMO2 through its SH3 domain (Fig. 6C) (31). Dock4-SH3 and SH3-L showed a similar binding ability to ELMO2 as Dock4-FL, suggesting that these fragments act as competitive binding partners of Dock4 (Fig.…”
Section: Expression Pattern Of Dock4 In the Brain-to Gain Insightsmentioning
confidence: 77%
“…It is well known that the binding partners of the Dock180 family of proteins function as Rac activators. The binding of ELMO relieves the inhibitory conformation of Dock 180 and exposes the binding domain for nucleotide-free Rac (42). The Armadillo repeats on the N terminus of ELMO work with another protein, RhoG, help to target the Dock180-ELMO complex to the membrane, where Rac is activated (43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…The amino-terminal 558 amino-acid residues (N-term) were necessary for targeting of the ELMO-Dock180 complex to the membrane 14,17 , whereas the carboxy-terminal 196 residues (C-term) were necessary for binding Dock180 and for optimal Rac activation 15,16 . Because the receptor(s) upstream of ELMO1 during engulfment were not known, we performed a yeast two-hybrid screen, with N-term as bait.…”
mentioning
confidence: 99%
“…Previous studies revealed two 'functional' regions within ELMO1 and its Caenorhabditis elegans homologue CED-12 during phagocytosis 5,[14][15][16][17] . The amino-terminal 558 amino-acid residues (N-term) were necessary for targeting of the ELMO-Dock180 complex to the membrane 14,17 , whereas the carboxy-terminal 196 residues (C-term) were necessary for binding Dock180 and for optimal Rac activation 15,16 .…”
mentioning
confidence: 99%